The new business road test : what entrepreneurs and investors should do before launching a lean start-up - Mullins, John W. (John Walker) (Pearson, 2018)
ROAD TEST YOUR IDEA BEFORE YOU LAUNCH YOUR LEAN START-UP Thinking about starting a new business? Stop! Is there a genuine market for your idea? Do you really want to compete in that industry? Are you the right person to pursue it? No matter how talented you are or how much capital you have, if you're pursuing a fundamentally flawed opportunity then you're heading for failure. So before you launch your lean start-up, take your idea for a test drive and make sure it has a fighting chance of working. Now in its fifth edition, The New Business Road Test is the essential handbook for anyone wan.